Influence of fecal microbial transplant (FMT) between male and female rats on methamphetamine-induced hyperthermia - Amal Aburahma; Emma L. Stewart; Srishti Rana; Ray Larsen; Christopher S. Ward; Jon E. Sprague (International Journal of Hyperthermia, 2023)
AbstractObjective To investigate the effect of bidirectional fecal microbial transplant (FMT) between male and female rats on methamphetamine (MA)-induced hyperthermia.Methods FMT was performed between male and female rats prior to MA (10 mg/kg, sc) treatment. Core body temperature, plasma drug and norepinephrine (NE) levels were measured and compared between treatment groups. 16S rRNA gene sequencing of bacterial communities between male and female rats was performed.Results MA treatment resulted in significantly higher core body temperatures in male groups (control and FMT-treated) compared to MA-treated female groups (control and FMT-treated). Plasma concentrations of MA and amphetamine were higher in females than males. Whereas, plasma norepinephrine (NE) levels were not different between male and female rats 90 minutes after MA treatment. At the phyla level, the microbiome of male and female control rats were dominated by Firmicutes and Bacteroidetes. Males had a higher relative abundance of Firmicutes and lower relative abundances of Bacteroidetes than females. The FMT procedure changed the recipient group towards their donor with males getting closer to their donors than females. In the control groups following MA treatment, Firmicutes increased and Bacteroides decreased in females and males. Conversely, in the FMT treatment groups following MA treatment, Firmicutes decreased while Bacteroidetes increased in females and males.Conclusions Although definite differences in the structure and diversity of the gut microbiome were observed using 16S rRNA gene sequencing of bacterial communities between male and female rats, these differences do not seem to contribute to the sex-based differences in MA-induced hyperthermia.